Ancient tales of giants from Qumran and Turfan contexts, traditions, and influences - Tales of Giants from Qumran and Turfan: Ancient Contexts, Traditions, and Influences 2014 Wessobrunn; Goff, Matthew J.; Stuckenbruck, Loren T. 1960-; Morano, Enrico 1951- (Tübingen Mohr Siebeck, 2016)
Cover -- Preface -- Table of Contents -- Matthew Goff: Introduction -- Part One: Gibborim and Gigantes. Antecedents, Reception, and Comparative Contextsfrom the Hebrew Bible and Greek Literature -- Brian R. Doak: The Giant in a Thousand Years: Tracing Narratives of Gigantism in the Hebrew Bible and Beyond -- I. The Embarrassing and Alluring Giant -- II. Five Categories of Giant Thinking in the Hebrew Bible -- 1. The giant as divine or semi-divine figure -- 2. The giant as anti-law and anti-king -- 3. The giant as elite adversary and elite animal
4. The giant as unruly or overgrown vegetation -- 5. The giant as the defeated past -- III. A Transition to the Early Jewish Giant -- IV. Conclusion -- Samantha Newington: Greek Titans and Biblical Giants -- Michael Tuval: "Συναγωγὴ γιγάντων" (Prov 21:16): The Giants in the Jewish Literature in Greek -- I. The Giants in the LXX -- II. The Wisdom of Solomon, 3 Maccabees, Baruch, 3 Baruch, Ben Sira, and the Testaments of the Twelve Patriarchs -- III. Pseudo-Eupolemus -- IV. The Sibylline Oracles -- V. Philo of Alexandria -- VI. Flavius Josephus -- VII. Summary and Conclusions
Part Two:Tales of Giants in their Ancient Jewish Context. The Dead Sea Scrolls, the Book of Watchers, and Daniel -- Joseph L. Angel: The Humbling of the Arrogant and the "Wild Man" and "Tree Stump" Traditions in the Book of Giants and Daniel 4 -- I. Introduction -- II. Parallels in Daniel 4 and the Book of Giants -- III. Explanations and Implications -- Amanda M. Davis Bledsoe: Throne Theophanies, Dream Visions, and Righteous(?) Seers: Daniel, the Book of Giants, and 1 Enoch Reconsidered -- I. Introduction -- II. The Throne Theophanies of Daniel 7, 4Q530, and 1 Enoch 14 -- 1. The Deity
2. The Throne(s) -- 3. The Attendants -- III. The Relationship between the Visions of Daniel 7, 4Q530, and 1 Enoch 14 -- IV. Dream Visions and the Role of the Seer in Daniel 7, 4Q530, and 1 Enoch 14 -- V. Conclusion -- Ida Fröhlich: Giants and Demons -- I. Demonic Traits of the Watchers -- II. Demonic Traits of the Giants -- III. Naming the Sons of the Watchers: Gibbōrîm -- IV. Genesis 6:1-4 and the Book of Watchers -- Matthew Goff: The Sons of the Watchers in the Book of Watchers and the Qumran Book of Giants: Contexts and Prospects -- I. Introduction: Questions, Contexts and Prospects
II. The Giants in the Book of Watchers -- III. The Giants in the Qumran Book of Giants -- IV. The Fate of the Giants -- V. Conclusion -- Loren T. Stuckenbruck: The Book of Giants among the Dead Sea Scrolls: Considerations of Method and a New Proposal on the Reconstruction of 4Q530 -- I. Introduction -- II. Methodological Considerations in Reconstructing the Qumran Book of Giants -- III. A Sequenced Outline Derived from Extant Dead Sea Fragments -- IV. A Proposal for Reconstructing the Remaining Length of 4Q530 -- V. Conclusion
Part Three: Enochic Traditions in Central Asia and China. Exploring Connections and Affinities betweenGiants in Ancient Judaism and Manichaeism
Description based upon print version of record
Keywords: Electronic books; Konferenzschrift -- 2014 -- Wessobrunn